2005
DOI: 10.1177/096739110501300606
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Thermal Properties of Oil Palm Empty Fruit Bunch-Filled Unplasticized Poly (Vinyl Chloride) Composites

Abstract: Awareness of the advantages of natural fibres has stimulated interest in their use to reinforce polymers. One type of natural fibre that is of great relevance to Malaysia is oil palm empty fruit bunches (EFB). To produce EFB-filled unplasticized poly(vinyl chloride) (PVC) composites, PVC resin and the various additives were first dry-blended using a laboratory blender before being milled into sheets on a two-roll mill. Test specimens were then hot pressed, after which the mechanical and thermal properties were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…The hydrogen bonds resulted in OPEFB fibers to agglomerate among them into fiber bundles, which consequently, lowered the contact area with the matrix and weakened the fiber-matrix interface. The weakness of interfacial adhesion resulted in debonding as identified by pulling-out of fiber bundles in the composites, as reported in the previous researches [12,13] .…”
Section: Fourier Transform Infrared Studymentioning
confidence: 77%
See 2 more Smart Citations
“…The hydrogen bonds resulted in OPEFB fibers to agglomerate among them into fiber bundles, which consequently, lowered the contact area with the matrix and weakened the fiber-matrix interface. The weakness of interfacial adhesion resulted in debonding as identified by pulling-out of fiber bundles in the composites, as reported in the previous researches [12,13] .…”
Section: Fourier Transform Infrared Studymentioning
confidence: 77%
“…The impact strength of composites decreased with increasing untreated OPEFB fiber content from 10 to 40 phr. As discussed in previous work [12] , this trend was associated with the poor wetting of the fiber by the PVC matrix, even though OPEFB has the ability to form a physical interaction with polar PVC. This interaction is relatively weak compared to the strong fiber-fiber interaction caused by hydrogen bonds.…”
Section: Fourier Transform Infrared Studymentioning
confidence: 84%
See 1 more Smart Citation
“…However, addition of kenaf had enhanced its thermal stability at the higher temperatures. Abu Bakar et al [6] reported EFB-filled unplasticized poly(vinyl chloride) (PVC) composites. They found http://dx.doi.org/10.1016/j.matdes.2014.09.027 0261-3069/Ó 2014 Elsevier Ltd. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…At low MAH content (from 0-4 php), the flexural strength values increased only from 16 to 29 MPa. At this stage, the composites have undergone degradation (Figures 4(d) and 4(e)), resulting an increase in the cleavage of Cl atoms in PVC and reducing the molecular stability [21]. This fact enhances the ability of polymer chains to slip past each other and more slippage of the molecular chains, causing a reduction in flexural strength.…”
Section: Flexural Behaviourmentioning
confidence: 99%